Nova (2007), volume 2 ebook Knowhere. - Abnett, Dan (Nova (2007), 2012)
Collects Nova #8-12 & Annual #1. We've seen Richard Rider burnt to a crisp, replaced by a Kree hottie and turned to the dark side. But just wait until you see what the last surviving space cop faces now! It's the Phalanx, the New Mutants' Warlock and more! Author: Dan Abnett, Andy Lanning. Illustrator: Paul Pelletier. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com